Constitutional Regulation of the Economy as a Specific Feature of Russian Constitutionalism - VINOGRADOVA, Elena Valeryevna; SHULCHENKO, Yury Leonidovich; MUKHLYNINA, Maria Mikhailovna; DOVGOLYUK, Natalia Vladimirovna; MATVEEV, Pavel Aleksandrovich (Journal of Advanced Research in Law and Economics, 2019)
The paper is devoted to the analysis of the specifics of the Russian constitutional regulation of the economy. It has been established that the absence of certain fragments of the evolution of the general constitutional theory in Russia prevents the understanding that the theory of economic constitution is not just an allegory, but a tool for the study of constitutional regulation. It has been proven that the basis for the study of constitutional regulation of economic relations within the theory of economic constitution is associated with the fact that constitutional provisions governing economic relations are considered as a certain set of interconnected by economic relations and imbued with internal unity systemic logical and legal connections. It has been determined that the main feature of the economic constitution is its integrity, coherence of its parts, which together create a new quality, not reduced to the characteristics of each individual part.